Pengaruh Financial Distress terhadap Earnings Management (Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek In-donesia Periode 2014-2018) - Ade Suryana; Muhammad Risyan Rizqi Khairi (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
Reflecting on the biggest accounting scandals in the world, such as the case of Bernie Medoff, Enron, Lehman Brother, Worldcom, and others; corporate stakeholders are powerless against the collapse of a company or economy. There is a practice of Earnings Management, where accounting practices are misused for the benefit of company management. Then, the emergence and bankruptcy of companies continued to alternate based on the number of bankruptcy cases in Indonesia. And the mining sector became an advanced industry in the era of Susilo Bambang Yudhoyono, but experienced a setback in the era of Joko Widodo. Many small companies went bankrupt and were acquired by large companies. Financial Distress pressure can make management to do Earnings Management based on certain motives (Diri, 2018). The study was conducted to find the relationship between Financial Distress through the Grover model and Earnings Management through the Modified Jones model. The results show that there is a relationship between Financial Distress and Earnings Management, the influence or strength of the explanation of Financial Distress on Earnings Management is at a strong level.